SUGGESTIVE TECHNIQUES IN EDUCATIONAL PROCESS - Желуденко, М. О.; Болотна, Т. М. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2015)
The article deals with the use of suggestive techniques for intensification of educational process. The main suggestive means directed at revealing reserve resources of an individual were determined; method of relaxopaedic education as the main method of suggestopaedic technique was analyzed; possibilities of using suggestive techniques in students teaching at different stages of studying in general and in the process of a foreign language studiing specifically were examined